Penanaman Pohon Sebagai Upaya Penghijauan Di Area Wisata Watu Tanjung Desa Sumber Wangi, Kecamatan Karang Bintang - Wibawa, I Gusti Nyoman Arya; Jannah, Arum Fatika; Aulia, Redhana; Hanifah, Miarti; Marinda, Rossa; Agustin, Dinda Nisa; Mukhlisin, Mukhlisin; Madian, Ali; Fradana, Iqbal (-, 2025)
KKN or Kuliah Kerja Nyata (Real Work Lecture) is a program implemented by universities as a form of implementation of the Tri Dharma of higher education. Students engaged in KKN activities directly interact with the community and help solve problems in the village. The planting of trees as an effort for greening in the tourist area of Watu Tanjung, Sumber Wangi Village, Karang Bintang Subdistrict, is part of the community service activities aimed at improving environmental quality and supporting the sustainability of the tourism sector. The background for this activity is to meet the increasing need for greening in tourist areas that have significant natural potential but are vulnerable to environmental damage. The objective of this service is to raise community awareness about the importance of greening and to make a tangible contribution to environmental preservation. The partner for this service activity is the community of Sumber Wangi Village, which is involved in the tree planting and maintenance process. The method used is a participatory approach, providing training to the community on effective greening techniques and how to care for plants. The results of the service show an increase in community awareness regarding the importance of a healthy environment, as well as the creation of green spaces that can attract tourists and enhance the aesthetics of the tourist area. This activity also successfully fostered good cooperation between the community and the local government. Overall, the results of this service indicate that greening in tourist areas has a positive impact on both the environment and the local economy. Therefore, greening activities like this are very important for the sustainability of ecosystems and the tourism sector.